Surgical outcomes of the closure of mesenteric defects in side-to-side jejunoileal anastomosis plus proximal loop ligation (SSJIBL) using absorbable and non-absorbable surgical sutures - Li, Yonglin; Wang, Jing; Wu, Chengyu; Lu, Xiaojing; Zheng, Qi; Wei, Rongwei; Zong, Ziliang; Chen, Yigang (Frontiers in Surgery, 2025)
BackgroundMesenteric hiatal hernia represents a significant complication following gastrointestinal surgery, and the closure of mesenteric defects has been shown to mitigate the risk of such hernias. SSJIBL, a surgical technique that has gained prominence in recent years, is widely acknowledged for its efficacy in glucose reduction and its association with fewer complications. Nevertheless, there remains a gap in the literature regarding the optimal suture choice for closing mesenteric defects, as no definitive studies or reports have addressed this specific issue to date. So we wanted to know what sutures we could use to more safely close the mesenteric defect.Materials and methods36 New Zealand rabbits were divided into three groups, NC, Absorbable suture and Non-absorbable suture. Group NC was not operated, group Absorbable suture close the mesenteric defect with absorbable suture, and group Non-absorbable suture close the mesenteric defect with non-absorbable suture; the rabbits were weighed and measured monthly, and after three months, the rabbits were observed to see if there was any internal hernia and to detect the tethered lacunae tension.ResultsAccording to the results of the experiment, both absorbable suture and non-absorbable suture can induce infiltration of inflammatory cells and enhance adhesion strength relative to the NC group.ConclusionBoth absorbable and non-absorbable sutures are safe and reliable.